Guidebook: Improved management practices for integrated rice-fish systems and dike cropping - Collis, William; Mokarrom, Hossain; Dr. Md. Mahbubul Alam, Miah; Sarker, Ashoke; Islam, Md. Mazharul; Roy, Sattyanarayan; Sarker, Parimal Chandra; Saha, Gopal Chandra; Zahura, Israt; Ali, Hazrat; Biswas, Ashutosh (WorldFish, 2023)
This training manual on “Improved management practices on rice-fish and dike cropping” offers guidance for organizing training sessions with pertinent farmers and extension workers. This publication provides an overview on Rice-Fish farming system including importance, advantage and disadvantage, type and technique of rice-fish culture and role of rice, fish, and vegetable in nutrition, livelihood, and economics. It also details the identification and preparation of land conducive to rice-fish and vegetable cultivation, in addition to providing guidance on rice cultivation management. The primary focus of this manual is to describe improved management techniques, including pre-stocking, stocking, and post-stocking procedures, for integrated rice-fish culture. Furthermore, it includes methods for cultivating vegetables on rice-fish plots, aiming to improve both farmers' profitability and nutritional outcomes.